PENGARUH STRUKTUR KEPEMILIKAN DALAM CORPORATE GOVERNANCE TERHADAP KEPUTUSAN PENDANAAN DAN EARNINGS MANAGEMENT - Pualam, Nigar Nuansa (Jurnal Akuntansi AKUNESA, 2014)
The company's ownership structure influence funding decisions and corporate earnings management. Institutional ownership can increase monitoring as a control company which affects the company's use of debt and limit the behavior of managers towards debt and financial reporting policies. Management ownership can align interests between the agent and the principal who gives new motivation agent in managing the company well. Alignment of the interests of agents may limit earnings management behavior of the agent and the company's use of debt. Institutional ownership and ownership of managers do not always have a positive impact on the company. Institutional ownership can lead to domination of possession which resulted in the takeover of power and expropriation. Ownership managers may also weaken the excessive monitoring of the company due to the company's right to the higher managers. Keyword: Institusional ownership, Manajerial ownership, Influence funding, Earnings management